Mixed speech at work: a case study - Pinkevičienė, Dalia (Taikomoji kalbotyra, 2017)
The paper delves into the situated usage of mixed speech produced by adult Lithuanians at work, the environment hardly ever sociolinguistically researched in Lithuania. By mixed speech, Lithuanian speech interspersed with occasional insertional elements from other languages is meant. The study aims to see how more diverse linguistic resources that are now available in Lithuania are used to construct and negotiate social relations and social identities in the talk at work. The case study, which is a part of an ongoing larger scale project on Lithuanian workplace discourse, draws on digital audio recordings of naturally occurring spontaneous conversations between employees collected by a volunteer in a media-related company in Vilnius. The recordings containing elements of languages other than Lithuanian (English and Russian) have been transcribed and analysed using Interactional Sociolinguistics (IS), an in-depth qualitative approach that combines the application of the interpretive methods of discourse analysis with insights into social and cultural issues. The paper argues that mixed speech in Lithuanian workplace discourse is creatively used as group or individual stylistic choice to construct certain social images and to perform various functions: for instance, mixed speech containing Russian insertions, slang and swear words serves as an index of belonging to the group (or a community of practice), whereas English is a necessary tool for doing well in a contemporary work environment and presenting oneself as an expert in one’s professional field; English insertions tend to be employed when things need to be quickly and efficiently done while Russian is still used more extensively for off-task talk, such as small talk, gossiping, humour and jokes, which constitute an integral part of the talk at work. It can be hypothesised, however, that the range of functions performed by English insertions is gradually expanding as the command of Russian among co-workers is decreasing. The study depicts mixed speech as a means of negotiating social identities of a friendly and supportive colleague, a skilled and experienced professional, a creative, playful and adaptive communicator, and an open-minded, educated and sophisticated person.
Keywords: workplace discourse; mixed speech; linguistic resources; English and Russian insertions; interactional sociolinguistics; indexical meanings